Intelligent Software Methodologies, Tools and Techniques : 13th International Conference, SoMeT 2014, Langkawi, Malaysia, September 22-24, 2014. Revised Selected Papers - Fujita, Hamido; Selamat, Ali.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the best papers selection from the proceedings of the 13th International Conference on Intelligent Software Methodologies, Tools and Techniques, SoMeT 2014, held in Langkawi, Malaysia, in September 2014. The 27 full papers presented were carefully reviewed, thoroughly revised or enlarged, and selected as best papers from the 79 published proceedings papers, which had originally been selected from 192 submissions. The papers are organized in topical sections on artificial intelligence techniques in software engineering; requirement engineering, high-assurance system; intelligent software systems design; creative and arts in interactive software design; software methodologies for reliable software design; software quality and assessment for business enterprise; software analysis and performance model; software applications systems.
Artificial intelligence techniques in software engineering -- Requirement engineering -- High-assurance system -- Intelligent software systems design -- Creative and arts in interactive software design -- Software methodologies for reliable software design -- Software quality and assessment for business enterprise -- Software analysis and performance model -- Software applications systems.
Keywords: Computer science; Software engineering; Artificial intelligence; Information Systems Applications (incl. Internet).; Computer Applications; Software Engineering; Artificial Intelligence; User Interfaces and Human Computer Interaction